2007
DOI: 10.3324/haematol.10516
|View full text |Cite
|
Sign up to set email alerts
|

The risk of recurrent venous thromboembolism after discontinuing anticoagulation in patients with acute proximal deep vein thrombosis or pulmonary embolism. A prospective cohort study in 1,626 patients

Abstract: While it has long been recognized that patients with acute unprovoked deep vein thrombosis (DVT) or pulmonary embolism (PE) have a higher risk of recurrent venous thromboembolism (VTE) than that of patients with secondary thrombosis, whether other clinical parameters can help predict the development of recurrent events is controversial. The aim of this investigation was to assess the rate of recurrent VTE after withdrawal of vitamin K antagonists, and to identify clinical parameters associated with a higher li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
518
9
31

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 692 publications
(587 citation statements)
references
References 34 publications
29
518
9
31
Order By: Relevance
“…The annual risk of recurrent VTE after a first idiopathic VTE is about 10% during the first 2 years, and then about 3%, which gives a cumulative recurrence rate of 20% at 3 years and 40% at 5 years. 18 Recently, a case-fatality rate for VTE after treatment discontinuation of 8% (idiopathic DVT) to 12% (idiopathic PE) could be established by Douketis et al 22 in a pooled analysis of the DURAC I study 9 and an Italian study 18 in more than 2000 patients who were followed for several years. On the other hand, annual risks of major bleeding have been reported in 2% to 12% in controlled studies, 24 or even 29% 25 in the RIETE Registry with a case-fatality rate of 10% 26 to 33%.…”
Section: Balancing the Risk Of Vte Recurrence And The Risk Of Bleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual risk of recurrent VTE after a first idiopathic VTE is about 10% during the first 2 years, and then about 3%, which gives a cumulative recurrence rate of 20% at 3 years and 40% at 5 years. 18 Recently, a case-fatality rate for VTE after treatment discontinuation of 8% (idiopathic DVT) to 12% (idiopathic PE) could be established by Douketis et al 22 in a pooled analysis of the DURAC I study 9 and an Italian study 18 in more than 2000 patients who were followed for several years. On the other hand, annual risks of major bleeding have been reported in 2% to 12% in controlled studies, 24 or even 29% 25 in the RIETE Registry with a case-fatality rate of 10% 26 to 33%.…”
Section: Balancing the Risk Of Vte Recurrence And The Risk Of Bleedingmentioning
confidence: 99%
“…Moreover, in this series, the recurrence rate was lower (5.5 per 100 patient-years, 95%CI: 3.7-7.8) than in the PROLONG study. In a similar attempt to better evaluate the risk of recurrence after a first DVT, Prandoni et al 18 showed that the presence of residual DVT is a risk factor for recurrent thromboembolism in patients with acute DVT. However, the exact instructions for use of either D-dimer or residual DVT remain to be established.…”
Section: Evaluating the Risk Of Thromboembolic Recurrencementioning
confidence: 99%
“…Whenever the model required data that could not be retrieved from the Hokusai-VTE trial, transition probabilities were derived from publications; these data included the probability of developing CTEPH [10] and PTS [11] after a VTE event, the probability of disability following ICH [12], some disease-specific mortality rates (due to a PE recurrence [13], the probability of dying when disabled from ICH [14], and short-term [15] and long-term mortality [16] from CTEPH), and the probability of developing rVTE while off treatment [17] (Table 2). The general mortality of the cohort depended on the gender distribution and mean age across the time horizon.…”
Section: Methodsmentioning
confidence: 99%
“…Blacks also had a higher proportion of idiopathic DVT and idiopathic PE compared with Whites, who more often had secondary, provoked VTE. This finding is ominous for Blacks because after discontinuing anticoagulation, those with idiopathic VTE have a much higher rate of recurrent events than those with provoked VTE [10].…”
mentioning
confidence: 92%